The trials and triumphs of co-producing an evaluation plan: A principles-focused evaluation - Holly Harris; Kayle Donner; Jordana Rovet; Elizabeth Rosell; Jacob Wolframe; Taryn Lee; Gail Bellissimo; Andrew Johnson; Sophie Soklaridis; Faisal Islam (Research Involvement and Engagement)
Abstract Background Recovery Colleges are mental health-oriented education programs that are rooted in principles of peer support and co-production. Co-production, in this context, involves people with lived experience of mental health and addiction challenges and people with other forms of expertise (e.g., mental health professionals, administrators, and researchers) collaborating on the design and actualization of programs and initiatives. Despite co-production being a central feature of Recovery Colleges, very few Recovery College evaluations appear to be co-produced. In addition, there is a lack of research that evaluates the quality of the co-production processes in developing evaluations. The Recovery College at the Centre for Addiction and Mental Health, called the Collaborative Learning College, established an Evaluation Subcommittee with the goal of co-designing and implementing an evaluation plan for the program. In response to the dearth of literature on co-producing Recovery College evaluations and the quality of such collaborative processes, the Evaluation Subcommittee conducted a principles-focused evaluation to assess the quality of their process of co-producing an evaluation plan. Methods All members of the Evaluation Subcommittee collaboratively developed and agreed on three principles that they felt were most important in their co-production process. Using a self-narrative approach, each member then produced a reflection on the importance of the principles, the degree to which the committee adhered to them, and the impact. Finally, members engaged in collaborative thematic analysis and co-wrote this manuscript. Results The results of this study outline member’s purposes for joining the Evaluation Subcommittee, the strengths and challenges related to embodying the collaborative principles, and the associated impacts. Conclusions The findings demonstrate the value of co-producing health education evaluations with people with lived experience and highlight important lessons learned through the Evaluation Subcommittee’s collaborative process, specifically related to mitigating the impacts of power imbalances. These lessons can be valuable for others to consider in their co-production processes.